(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper explores various methodologies for teaching English as a foreign language. It examines traditional and modern approaches, their effectiveness in developing students’ linguistic skills, and the role of technology in enhancing learning outcomes. The study aims to provide practical recommendations for teachers to improve classroom instruction and student engagement.